Serum CEA Level in Predicting Liver Metastases of Colorectal Cancer Among Young Adult Patients - Sihotang, Ely S.P; Putranto, Agi S (The New Ropanasuri Journal of Surgery, 2022)
Introduction: Incidence and mortality of CRC are currently increasing in those under 50 years. The study aims to determine the predictive value of serum CEA levels as the liver metastases predictor of colorectal cancer (CRC) in young adults. Methods: A cross-sectional study was conducted using secondary data (patient medical records) from 2015–to 2021. Patients aged <50 years who were diagnosed histopathologically with primary colorectal cancer at dr. Cipto Mangunkusumo General Hospital (CMGH) were recruited. We excluded patients with a history of other malignancies, who had undergone operative management for colorectal cancer, and preexisting liver disease. The outcome of this study is the cut-off of the CEA value obtained by the ROC curve and the sensitivity and specificity of the CEA value in predicting CR liver metastases. Results: Out of 181 subjects enrolled, a total of 43.6% were female. Fifty-nine subjects (32.6%) had liver metastases. The CEA level of the metastases group was 208.1 (2.1–12503.2) ng/mL; this was much higher than the non-metastases group, which was 6.27 (0.8– 1099.4) ng/mL (p <0.001). The AUC value was at 0.904, and the CEA level cut-off was 38.765 ng/mL (Youden's Index = 1.718). The sensitivity and specificity were 91.53% (91.5 CI, 81.32%– 97.19%) and 80.3% (72.16%– 86.97%), respectively. The odds ratio of young colorectal cancer patients having liver metastases was 44.10 (95% CI, 15.92–122.20). Conclusion: CEA level ≥38.765 ng/mL has good sensitivity and specificity in predicting liver metastases among young adults with CRC.